Neuroinflammation of microglia polarization in intracerebral hemorrhage and its potential targets for intervention - Yang, Guoqiang; Fan, Xuehui; Mazhar, Maryam; Guo, Wubin; Zou, Yuanxia; Dechsupa, Nathupakorn; Wang, Li (Frontiers in Molecular Neuroscience, 2022)
Microglia are the resident immune cells associated with central nervous system (CNS) diseases, including intracerebral hemorrhage (ICH), ischemic stroke, etc. It has been well verified that microglia are activated to acquire different inflammatory phenotypes, including pro-inflammatory and anti-inflammatory phenotypes, which act as a crucial character in the neuroinflammation after ICH. After ICH onset, pro-inflammatory mediators produced by microglia at the early stages suppress the anti-inflammatory effects of microglia. It has been verified that inducing microglia into an anti-inflammatory phenotype could alleviate inflammatory response and engulf cellular debris. This review will elucidate the dynamic profiles of different microglia phenotypes and their switch-induced available shift following ICH. The results can facilitate an understanding of the self-regulatory functions of the immune system involving the shift of microglia phenotypes in ICH. Moreover, suggestions for future preclinical and clinical research and potential intervention strategies are provided.